Percolation-Modeling Comparison Between the Conductivities of Zinc-Graphene Quantum Dot Nanocomposite and Graphite during Extracellular Electron Transfer in Microbial Fuel Cell Electrodes - Biscocho, Jamme Omar A. (Animo Repository, 2023)
While promising as an energy production alternative through its sustainability and wastewater treatment utility, a microbial fuel cell is not widely used due to its low power output and high cost. The development of advanced electrode materials is currently being pursued to solve this problem. A zinc-graphene quantum dot nanocomposite was modeled using percolation theory as a prospective advanced electrode material. During extracellular electron transfer, the electrical conductivity properties of the material were studied through cellular percolation models, percolation probability functions, and electrical conductivity curves. These models were compared against those of the conventional graphite electrodes and the leading graphene electrodes. The nanocomposite was found to conduct at low probabilities of open sites and exhibit the highest electrical conductivity of the three materials for the longest duration across the interval. Based on the models, Zn-GQD was demonstrated to be an ideal MFC electrode material for its balance between the early onset of conduction and decently high electrical conductivity.